SYNCRETISM OF ISLAM AND LOCAL CULTURE IN THE MAKKULIWA LOPI RITUAL IN SABANG SUBIK POLEWALI MANDAR - Muliadi, Muliadi; Wahyudi AR, Nirwan; bin Mahsyar, Ahmad Dhiyaul Haq (Al-Qalam, 2024)
This article presents the research findings from a qualitative phenomenological approach on the syncretism of Islam and local culture in the makkuliwa lopi ritual in Sabang Subik Polewali Mandar. The syncretism of religion and local culture in the makkuliwa lopi ritual is manifested in two processes. First, the syncretization of motives, goals, or intentions. For example, the fishermen's habit of serving traditional food was originally related to ceremonies for the worship of supernatural beings. This habit is maintained without undergoing physical changes, but a shift in orientation towards worship of Allah SWT. In this case, there is a syncretization of the motives/goals/intentions of the makkuliwa lopi ritual. Second, the syncretization of the makkuliwa lopi ritual process. This process involves aligning traditional ritual elements with Islamic norms or sharia. Islam influences the adaptation of prayers or mantras, the actors involved in the rituals, as well as a series of makkuliwa lopi rituals which are syncretized according to Islamic principles. The makkuliwa lopi ritual in Sabang Subik Polewali Mandar has a positive impact in the socio-religious dimension which, among other things, can be observed from the community's moderate religious attitude, close social cohesion, and the potential it offers for the economic development of the people. Thus, the ritual acts as a catalyst for positive growth in various aspects of local community life.